Modified field test for determining the specific endurance in rhythmic gymnastics - Gateva, M. (Journal of Applied Sports Sciences, 2019)
Several attempts have been made in the past years to create adequate tests in order to determinate the fitness level of the athletes in the gymnastics disciplines. Considering the high-intensity movements and the total routine time, we hypostatized that anaerobic metabolism is a determinant for rhythmic gymnastics performance. Based on the physiological indicators of a competitive routine the aim of this study was to create a reliable and valid specific field test to measure the fitness level (specific endurance) of the rhythmic gymnasts competing at national and international level. 12 high level gymnasts aged 15.7 ± 2.1 were involved in this study. The testing was done twice - once in the preparatory and second time in the competitive period. Two tests were performedin the field - the specific anaerobic test and a competitive routine. The heart rate and the bloodlactate were recorded during and after the load. Specific endurance gymnastics field test is a simple routine including specific but very basic rhythmic gymnastics exercises from each body group- steps; waves; balances; pivots; leaps and acrobatic elements with very low level of difficulties.The maximal blood lactate concentration levels recorded in both tests and periods did notshow any significant difference and varied between 7.2 to 8.4 mmol/l. All of the heart rate values after the loads indicated high work intensity - above 185 bpm. There were significant differences in both exercises (specific test & routine) between the preparatory and the competitive routine. The heart rate clearly showed adaptation of the cardiovascular system towards the load when tapering into the peak performance period. The suggested test is a standard field test suitable for active, mid to high level rhythmic gymnasts aged above 12 years which can measure the current specific endurance of a gymnast and compare it with her previous testing or gymnasts.